دراسة الشريان الرحمي بالايكو دوبلر للتنبؤ بالانسمام الحملي - جركس, عامر; صالح, حسن; جاموز, رفاه (Latakia University Journal -Medical Sciences Series, 2018)
Introduction : Preeclampsia is a common cause of maternal death . Inadequate trophoblastic invasion of the maternal spiral arteries plays a major role in the pathogenesis of preeclampsia . Doppler of uterine artery permits a non-invasive method for evaluation of the uteroplacental circulation . Aim : To study the role of uterine artery notch and resistive index (RI) on color Doppler ultrasound in prediction of preeclampsia. Materials and Methods :This is a prospective study conducted in Radiology Department at Tishreen and Al-Assad University Hospitals , Lattakia , Syria , during the period between June 2016 and June 2017. A total of 110 pregnant women at 24-26 weeks of gestation were enrolled in the study . The women were divided into 2 groups ; high risk and low risk groups for preeclampsia . Doppler ultrasonography was performed for them for evaluation of uterine artery notching and resistive index (RI). The pregnant women were followed until the end of gestation and the incidence of preeclampsia was documented . Sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of Doppler ultrasonography of the uterine artery, for the prediction of preeclampsia were assessed . Results : Preeclampsia has developed in 61.8% of high risk group and in 11.8% of low risk group . Sensitivity , specificity , PPV and NPV of abnormal uterine artery Doppler study for prediction of preeclampsia were 85.1% , 72.4% , 83.3% , and 75% in high-risk and 100% , 86.6 % , 50% and 100% in low-risk group, respectively. Notch and RI had a significant role in predicting preeclampsia in both groups of pregnant women , sensitivity and specificity had increased when they were used in combination . Conclusion : Doppler of uterine artery at 24-26 weeks of gestation can be used as a reliable screening test for prediction of preeclampsia and helps to identify women at high risk and helps to modify follow up and management. مقدمة : يعد الانسمام الحملي سبباً شائعاً للوفيات الوالدية . يلعب الغزو الأرومي الشاذ للشرايين الرحمية الحلزونية دوراً هاماً في الآلية الإمراضية للانسمام الحملي . إن دوبلر الشريان الرحمي هو طريقة غيرغازية لتقييم الدوران الرحمي المشيمي . هدف البحث : دراسة دور الثلمة ومشعر المقاومة بالدوبلر الملون للشريان الرحمي في التنبؤ بحدوث الانسمام الحملي . المواد و الطرق : دراسة مستقبلية أُجريت في قسم التشخيص الشعاعي والتصوير الطبي في مشفيي الأسد و تشرين الجامعيين , اللاذقية , سوريا , في الفترة الممتدة من حزيران 2016 حتى حزيران 2017 . شملت الدراسة 110 امرأة حامل بعمر حملي 24- 26 أسبوع حملي . تم تقسيم النساء إلى مجموعتين : مرتفعات الخطورة و منخفضات الخطورة للانسمام الحملي . تم إجراء تصوير إيكوغرافي بالدوبلر للشريان الرحمي لجميع الحوامل لتقييم وجود الثلمة و مشعر المقاومة . تمت متابعة الحوامل حتى نهاية الحمل و توثيق حدوث الانسمام الحملي . قمنا بتقييم الحساسية , النوعية , القيمة التنبؤية الإيجابية (PPV) , و القيمة التنبؤية السلبية (NPV) لدوبلر الشريان الرحمي للتنبؤ بحدوث الانسمام الحملي . النتائج : تطور الانسمام الحملي عند 61% من الحوامل ذوات الخطر المرتفع للانسمام و 11.8% من الحوامل ذات الخطر المنخفض . في مجموعة الخطر المرتفع كان دور دوبلر الشريان الرحمي للتنبؤ بحدوث الانسمام الحملي : حساسية , نوعية , PPV , و NPV : 85.1% , 72.4% , 83.3% , و 75% على الترتيب . و في مجموعة الخطر المنخفض : 100% , 86.6% , 50 % , و 100% على التريب . يمتلك كلٌّ من الثلمة و مشعر المقاومة دوراً هاماً للتنبؤ بحدوث الانسمام الحملي عند مجموعتي الحوامل , وتزداد حساسية و نوعية الدوبلر عند مشاركتهما معاً . الخلاصة : يمكن الاعتماد على دوبلر الشريان الرحمي في الأسبوع 24 – 26 من الحمل كاختبار مسح فعال للتنبؤ بحدوث الانسمام الحملي و تحديد الحوامل ذوات الخطر العالي لحدوثه و بالتالي تغيير خطة المتابعة و العلاج .